IDEOLOGI YANG MEMENGARUHI PENGELOLAAN RESOR WISATA NUSA DUA, BALI - I Gusti Ketut Purnaya; Francisca Titing Koerniawaty (Institut Pariwisata dan Bisnis Internasional, 2016)
Management of Nusa Dua Tourism Resort can not be separated from macro social and political developments at the national level and the micro at the regional level. The stakeholder power relations between the three pillars of the government (BTDC), investors, and the society in the management of Nusa Dua resort is influenced by external factors is the globalization that developing very fast. This study focused on analyzing and answering the basic of what ideology is affecting the management of Nusa Dua Tourism Resort. Results of this study indicate that the management of Nusa Dua Tourism Resort not only determined by the business management matters but also by the social and political situation and by global and others tourism related ideologies. Social and political change and demands by these ideologies force all three pillars in the Nusa Dua Tourism Resort management activities to wisely exercising their power in relation of each other for the benefit of all parties and assurance of the sustainability of the resort.IDEOLOGI YANG MEMENGARUHI PENGELOLAAN RESOR WISATA NUSA DUA, BALI